Species diversity and phylogeography of Cornus kousa (Asian dogwood) captured by genomic and genic microsatellites. Issue 15 (11th July 2020) - Nowicki, Marcin; Houston, Logan C.; Boggess, Sarah L.; Aiello, Anthony S.; Payá‐Milans, Miriam; Staton, Margaret E.; Hayashida, Mitsuhiro; Yamanaka, Masahiro; Eda, Shigetoshi; Trigiano, Robert N.
Abstract: Cornus kousa (Asian dogwood), an East Asia native tree, is the most economically important species of the dogwood genus, owing to its desirable horticultural traits and ability to hybridize with North America‐native dogwoods. To assess the species genetic diversity and to better inform the ongoing and future breeding efforts, we assembled an herbarium and arboretum collection of 131 noncultivated C. kousa specimens. Genotyping and capillary electrophoresis analyses of our C. kousa collection with the newly developed genic and published nuclear genomic microsatellites permitted assessment of genetic diversity and evolutionary history of the species. Regardless of the microsatellite type used, the study yielded generally similar insights into the C. kousa diversity with subtle differences deriving from and underlining the marker used. The accrued evidence pointed to the species distinct genetic pools related to the plant country of origin. This can be helpful in the development of the commercial cultivars for this important ornamental crop with increased pyramided utility traits. Analyses of the C. kousa evolutionary history using the accrued genotyping datasets pointed to an unsampled ancestor population, possibly now extinct, as per the phylogeography of the region. To our knowledge, there are few studies utilizing the same gDNA collection to compare performance of genomic and genic microsatellites. This is the first detailed report on C. kousa species diversity and evolutionary history inference. Abstract : Cornus kousa (Asian dogwood) is the most economically important species of the dogwood genus, owing to its desirable ornamental traits and ability to hybridize with North America‐native flowering dogwoods. To assess the species genetic diversity and to better inform the ongoing and future breeding efforts, we genotyped a collection of noncultivated C. kousa from US herbaria and arboreta samples using genomic an genic microsatellites. The data pointed to the species distinct genetic pools related to the tree country of origin, and informed the species phylogeographic history, which can help future breeding efforts.